Eco Enzim sebagai Larutan Pendukung untuk Menurunkan TSS dan COD Pada Air Limbah Tahu dengan Proses Anaerob - Yohanes Felix Ardiansyah; Mohamad Mirwan (Jurnal Serambi Engineering, 2024)
One type of liquid waste that is commonly encountered is waste from the tofu production process. Tofu production waste contains organic matter and chemical compounds that can pollute the environment if not properly managed. The increase in the amount of liquid waste generated is due to the growing human population and increasing industrial activities. Eco enzyme, which is produced by simple fermentation of fresh vegetable or fruit organic waste, molasses and water in a ratio of 1:3:10, has been shown to be beneficial in reducing pollution levels. Therefore, the objective of this study was to evaluate the potential of Eco enzyme as a supporting solution in reducing TSS and COD content in wastewater from tofu industry through anaerobic process. In this study, variation of anaerobic process was used by mixing Eco enzyme solution at 5%, 10% and 15% concentration. Anaerobic process was carried out with retention time of 5, 10 and 15 days. The results showed that fruit Eco-enzyme was more effective than vegetable Eco-enzyme. Anaerobic process with 5% concentration was able to reduce the pollutant parameters with the highest efficiency, which was 6.17% for TSS parameters and 89.17% for COD parameters on the 15th day of detention.